2019
DOI: 10.21273/hortsci13512-18
|View full text |Cite
|
Sign up to set email alerts
|

Target-site Mutation and Fitness Cost of Acetolactate Synthase Inhibitor-resistant Annual Bluegrass

Abstract: Annual bluegrass (Poa annua L.) is an annual weed that is particularly troublesome in managed turfgrass. It has been controlled conventionally with herbicides, including acetolactate synthase (ALS) inhibitors. However, resistance to ALS inhibitors has been documented throughout the southeastern United States since 2012. A rateresponse trial was conducted to confirm and determine the resistance level of suspected resistant P. ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In addition to this, some weeds have developed resistance to multiple modes of action while others have (developed decreased sensitivity to herbicides [21][22][23]. Both target-site and non-target-site mutations in the herbicide-resistant weeds have been reported [24,25]. These observations indicate over-reliance on herbicides as a non-sustainable measure for weed control.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, some weeds have developed resistance to multiple modes of action while others have (developed decreased sensitivity to herbicides [21][22][23]. Both target-site and non-target-site mutations in the herbicide-resistant weeds have been reported [24,25]. These observations indicate over-reliance on herbicides as a non-sustainable measure for weed control.…”
Section: Introductionmentioning
confidence: 99%
“…(or other weed species) and some of these mutations may carry fitness cost (Panozzo et al, 2021). One example is the 60% reduction in grain yield of ALS-resistant annual bluegrass harboring L574W mutation (Tseng et al, 2019). At this point, G5 plants are not yet resistant to the full dose of imazethapyr.…”
Section: Imazethapyrmentioning
confidence: 99%
“…Conversely, fitness cost has also been reported for glyphosate-resistant goosegrass (Eleusina indica (L.) Gaertn.) and imazethapyr-resistant annual bluegrass (Poa annua L.) which exhibited 5% and 60% reduction in seed production, respectively (Han et al, 2017;Tseng et al, 2019) but such cases are rarely observed in the field. Quinclorac-resistant junglerice from Arkansas, USA, does not exhibit fitness cost (Penka, 2018) and no fitness penalties have been reported for glufosinate-or FPBresistant weeds thus far.…”
Section: Introductionmentioning
confidence: 99%
“…TSR is due to a deletion of an amino acid or substitutions of different amino acids in the herbicide target protein, which may prevent the occurrence of herbicide interactions (Dayan et al 2018; Kukorelli et al 2013; Petit et al 2010). Target-site mutations contribute to P. annua resistance to ACCase, ALS, microtubule-assembly, PSII, and EPSPS inhibitors (Barua et al 2020; Cross et al 2015; Délye and Michel 2005; McElroy et al 2013; Svyantek et al 2016; Tseng et al 2019). Target-site mutations reported for mitotic-inhibiting herbicides confer resistance to the dinitroaniline herbicides.…”
Section: Introductionmentioning
confidence: 99%